2016
DOI: 10.1515/jppr-2016-0051
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of niclosamide on inhibition of bacterial leaf blight in rice

Abstract: Bacterial leaf blight is one of the major diseases in rice and affects yields. Thus, various methods have been applied to protect rice from this disease. Here, we show systemic translocation of the human drug niclosamide (5-chloro-N-(2-chloro-4-nitrophenyl)- 2-hydroxybenzamide) in rice and its long-term effect on prevention of rice leaf blight. The development of Xanthomonas oryzae pv. oryzae-induced rice leaf blight was effectively inhibited in untreated systemic leaves as in niclosamide-treated leaves, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(29 reference statements)
2
2
0
Order By: Relevance
“…Our in vivo experiment further demonstrated that niclosamide can effectively block the growth of Xoo thereby impeding the development of bacterial blight disease in rice plants ( Figures 1E,F ). This observation was consistent with the findings of Kim et al (2016a , b ) where they also showed that niclosamide has no harmful effect on the overall vegetative/reproductive growth and yield of the rice plant. In addition, they also showed that niclosamide can induce the expression of defense-related genes including salicylic and jasmonic acid hormones related genes in rice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our in vivo experiment further demonstrated that niclosamide can effectively block the growth of Xoo thereby impeding the development of bacterial blight disease in rice plants ( Figures 1E,F ). This observation was consistent with the findings of Kim et al (2016a , b ) where they also showed that niclosamide has no harmful effect on the overall vegetative/reproductive growth and yield of the rice plant. In addition, they also showed that niclosamide can induce the expression of defense-related genes including salicylic and jasmonic acid hormones related genes in rice.…”
Section: Discussionsupporting
confidence: 92%
“…According to the earlier reports ( Kim et al, 2016a , b ), we first confirmed the antibacterial activity of niclosamide against two pathogenic Xanthomonas oryzae pv. oryzae strains PXO99 and GDIV corresponding to race 6 and race 4 respectively.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…BLB is spread worldwide [22][23][24] and can cause as high as 60% reduction in rice yield in severe epidemics [16,23,25]. This vascular disease starts with the infection of rice leaves or roots by the Xoo bacterium through hydathodes (specialized pores present at the leaf margin where vascular supply ends), natural plant openings, such as stomata, and wounds [25][26][27]. Xoo multiplies and spreads within the xylem, causing long, grey to white opaque necrotic lesions that typically spread from the tip of a rice leaf [26,28].…”
Section: Introductionmentioning
confidence: 99%